Paws to remember - Kelly, Sofie, 1958- (Kelly, Sofie, 1958- Magical cats mystery., 2023)
"When a water leak repair results in a body being found behind the walls of the store run by the artists' co-op that Kathleen's friend Maggie is part of, everyone is completely mystified as to whose body it is and who hid it there. But as the dust settles, Kathleen's boyfriend, Detective Marcus Gordon, begins to suspect that the body could belong to a young woman who disappeared more than thirty years ago. When a friend with a connection to the young woman asks Kathleen to look into the circumstances around the disappearance, she and her cats--who have a special feline talent for catching felons--find themselves digging up secrets that at least one person in Mayville Heights would much prefer stay buried" --